Bacterial resistance genetic markers (fluoroquinolone, aminoglycosideo, macrolideo) - Antonio Linkoln Alves Borges Leal; Gabryella Karolliny Antunes Araujo; Samuel Martins Ribeiro Neto (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2020)
Bacterial resistance is a natural biological phenomenon, defined as an ability to multiply the presence of high temperatures of antimicrobials reached in therapeutic doses. Currently, there has been a large increase in the number of deaths related to hospital infections, being closely linked to resistant microorganisms. Knowledge of the genes responsible for the expression of resistance in the presence of high doses of antibiotics is of great importance, as it favors a more effective treatment, with the correct use of drugs and with a response effect in much less time, in addition to reducing levels of new cases of bacterial resistance. The objective of this work is to present high knowledge about the genetic markers of resistance in the main classes of antibiotics, fluoroquinolone, aminoglycoside and macrolides, using articles, technical manuals that describe the genetic markers of resistance. Different types of genes, plasmids and/or resistance markers to the main antibiotics. It can highlight what the work has to do precisely on the main genes expressed, when in contact with the antibiotics selected at work.